2017
DOI: 10.1038/s41598-017-08194-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid amplification of four retrotransposon families promoted speciation and genome size expansion in the genus Panax

Abstract: Genome duplication and repeat multiplication contribute to genome evolution in plants. Our previous work identified a recent allotetraploidization event and five high-copy LTR retrotransposon (LTR-RT) families PgDel, PgTat, PgAthila, PgTork, and PgOryco in Panax ginseng. Here, using whole-genome sequences, we quantified major repeats in five Panax species and investigated their role in genome evolution. The diploids P. japonicus, P. vietnamensis, and P. notoginseng and the tetraploids P. ginseng and P. quinque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Tetraploids P. ginseng and P. quinquefolius formed~2.59 MYA (Figure 2a). Five uniquely enriched LTR-RT families (PgDel, PgTat, PgAthila, PgTork and PgSire;Choi et al, 2014;Jang et al, 2017;Lee et al, 2017a) occupy >50% of the genome. PgDel LTR-RTs largely account for genome size variation among seven Panax species (Figure 2b,e).…”
Section: Genome Structure and Evolutionmentioning
confidence: 99%
“…Tetraploids P. ginseng and P. quinquefolius formed~2.59 MYA (Figure 2a). Five uniquely enriched LTR-RT families (PgDel, PgTat, PgAthila, PgTork and PgSire;Choi et al, 2014;Jang et al, 2017;Lee et al, 2017a) occupy >50% of the genome. PgDel LTR-RTs largely account for genome size variation among seven Panax species (Figure 2b,e).…”
Section: Genome Structure and Evolutionmentioning
confidence: 99%
“…This observation indicates a burst of Athila LTR element linked with Lolium speciation. It is known, that activation and integration of transposable elements may occur, e.g., due to environment change, lead to a rapid burst in a species-specific manner [45,46,56] and impact the evolution and speciation [45,57]. In some species, rapid increase of lineage-specific retroelements can also result in significant genome upsizing [23,[57][58][59], which was not observed in fescues and ryegrasses included in our study.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, our studies revealed the evolution of major repeats in Panax genus Lee et al 2017). We also provided distribution pattern of these major repeats and established chromosome identification system using these repeats .…”
Section: Discussionmentioning
confidence: 98%